Destabilized 3’UTR elements therapeutically degrade ERBB2 mRNA in drug-resistant ERBB2+ cancer models - Awah, Chidiebere U.; Glemaud, Yana; Levine, Fayola; Yang, Kiseok; Ansary, Afrin; Dong, Fu; Ash, Leonard; Zhang, Junfei; Ogunwobi, Olorunseun O. (Frontiers in Genetics, 2023)
Breast, lung, and colorectal cancer resistance to molecular targeted therapy is a major challenge that unfavorably impacts clinical outcomes leading to hundreds of thousands of deaths annually. In ERBB2+ cancers regardless of the tissue of origin, many ERBB2+ cancers are resistant to ERBB2 targeted therapy. We discovered that ERBB2+ cancer cells are enriched with poly U sequences on their 3’UTR which are mRNA stabilizing sequences. We developed a novel technology, in which we engineered these ERBB2 mRNA stabilizing sequences to unstable forms that successfully overwrote and outcompeted the endogenous ERBB2 mRNA encoded message and degraded ERBB2 transcript which led to the loss of the protein across multiple cancer cell types both in the wildtype and drug resistance settings in vitro and in vivo, offering a unique safe novel modality to control ERBB2 mRNA and other pervasive oncogenic signals where current targeted therapies fail.